Floristic composition and endemism pattern of vascular plants in Ethiopia and Eritrea. Issue 1 (12th August 2019) - Wang, Sheng‐Wei; Boru, Biyansa Hirpo; Njogu, Antony Waigwa; Ochola, Anne Christine; Hu, Guang‐Wan; Zhou, Ya‐Dong; Wang, Qing‐Feng
Abstract: Traditional attempts to delineate floristic regions are typically based on the qualitative analysis of species distribution, often ignoring the phylogenetic relationships among their taxa. Ethiopia and Eritrea are in the Horn of Africa, known as one of the world's biodiversity hotspots. We quantitatively classified the flora of Ethiopia and Eritrea into meaningful geographical units by analyzing the taxonomic and phylogenetic β‐diversity at genera, total species, and endemic species levels at a scale of 0.5° × 0.5° grid cells. Hierarchical clustering was used to quantitatively delimitate the flora and analysis of similarities was used to test the significant difference between the derived groups in taxonomic composition and phylogenetic relatedness. In total, two floristic subprovinces, five floristic districts, and 13 floristic subdistricts, as well as three centers of species endemism associated with three floristic subdistricts were identified. Our results also showed that the species diversity, endemism, and turnover of the highlands in Ethiopia and Eritrea were much higher than the lowlands, indicating that the floristic differences are closely related to the topography of the East African Rift. In this study, we provided a scientific framework for the composition and relationships of the floristic units in the Horn of Africa, and similarly provided a scientific basis for better conservation of the diversity in this region.